Między archiwum a bazą danych – o doświadczeniu sztuki nowych mediów - Szykowna, Sylwia (Studia Europaea Gnesnensia, 2019)
The essential objective of this paper is to examine the category of archive from the perspective of new media, which transform the model of linear his-torical discourse into a new one, whereby it assumes the form of a database, enabling novel modes of indexing reality